Farnesoid X receptor‐α is a proviral host factor for hepatitis B virus that is inhibited by ligands in vitro and in vivo. Issue 2 (11th October 2018) - Mouzannar, Karim; Fusil, Floriane; Lacombe, Benoît; Ollivier, Anaïs; Ménard, Camille; Lotteau, Vincent; Cosset, François-Loïc; Ramière, Christophe; André, Patrice
ABSTRACT: Hepatitis B virus (HBV) infection and bile acid (BA) metabolism are interdependent: infection modifies the expression of the BA nuclear receptor farnesoid X receptor (FXR)‐α, and modulation of FXRα activity by ligands alters HBV replication. Mechanisms of HBV control by FXRα remain to be unveiled. FXRα silencing in HBV‐infected HepaRG cells decreased the viral covalently closed circular (ccc)DNA pool size and transcriptional activity. Treatment with the FXRα agonist GW4064 inhibited FXRα proviral effect on cccDNA similarly for wild‐type and hepatitis B viral X protein (HBx)–deficient virus, whereas agonist‐induced inhibition of pregenomic and precore RNA transcription and viral DNA secretion was HBx dependent. These data indicated that FXRα acts as a proviral factor by 2 different mechanisms, which are abolished by FXRα stimulation. Finally, infection of C3H/HeN mice by a recombinant adeno‐associated virus‐2/8‐HBV vector induced a sustained HBV replication in young mice in contrast with the transient decline in adult mice. Four‐week GW4064 treatment of infected C3H/HeN mice decreased secretion of HBV DNA and HB surface antigen in adult mice only. These results suggest that the physiologic balance of FXRα expression and activation by bile acid is a key host metabolic pathway in the regulation of HBV infection and that FXRα can be envisioned as a target for HBV treatment.—Mouzannar, K., Fusil, F., Lacombe, B., Ollivier, A., Ménard, C., Lotteau, V., Cosset, F.‐L., Ramière, C., André, P. Farnesoid X receptor α is a proviral host factor for hepatitis B virus that is inhibited by ligands in vitro and in vivo. FASEB J. 33, 2472–2483 (2019). www.fasebj.org